Memórias da docência: o percurso formativo da professora Maria Salete Van Der Poel na educação popular (1960-1970) - Silva, Luziel Augusto da (2022)
This research analyzed the formative path of teacher Maria Salete Van Der Poel, considering her teaching trajectory and the memories of her experiences in Popular Education in the years 1960-1969, seeking to understand the history of teaching and Popular Education in Paraíba in the 1960s. , a period marked by socioeconomic changes, social problems - high rates of illiteracy and the lack of popular participation in the country's decisions - and the emergence of social and cultural movements driven by the intellectual segments of the northeast, mainly from Pernambuco, Paraíba and Rio Grande do Norte . Methodologically, this is a biographical research that was carried out from bibliographic, oral and documentary sources. And for the analysis of these materials, we used document analysis, performing an interpretation of the data in the light of the theoretical framework. The results made it possible to perceive that the teacher's training course was constituted by several sociopolitical confrontations (authoritarian government/Military Regime and social movements/progressive ideas), educational ideological clashes (educational policy aligned with capital, a conception of education based on capitalism and military government and the emergence of Paulo Freire's thought and his conception of liberating education) and professional statements (affirmation as a teacher, activist and popular educator). As well, it contributed to the understanding of teaching in spaces of Popular Education.